DYNAMICS OF ENCRYPTION AND CYBER SECURITY POLICY IN INDONESIA AS A SOCIO-CULTURAL CHANGE IN THE CYBER AGE - M. Prakoso Aji (Jurnal Scientia, 2023)
Socio-cultural changes that occur in society will affect the dynamics of a policy implemented by the government. The policy can be said as a cultural product because in its development, it is also necessary to pay attention to the socio-cultural values that exist in society. The dynamics of encryption and cybersecurity policies in Indonesia also need to adapt to socio-cultural values. Technological changes can affect public acceptance of a previously controversial policy. Still, in line with the needs and challenges faced in the cyber era, the community can only accept this policy. This process certainly takes a long time. In terms of encryption and cyber security policies, there are pros and cons in society, and political parties related to the MoU entered into by KPU Lemsaneg in 2013 caused the MoU cancellation. However, in 2021 a memorandum of understanding will be held between KPU and BSSN, which will not raise pros and cons. This is interesting to study in more depth. This paper wants to see how a policy must also consider socio-cultural change aspects. The method used is qualitative with literature study.